A study on hybrid cryptosystem: Pretty Good Privacy (PGP) / Hilmi Harun - Harun, Hilmi (2003)
Recent advances in computing power and recent interest in this privacy issue have led to the development of techniques to store sensitive information by using mathematics to encrypt and decrypt data. This technique enables us to store sensitive information or transmit it across insecure networks like the Internet so that it cannot be read by anyone except the intended recipient. This is what we called as cryptography. With the combination of some cryptosystem such as conventional cryptography and public key cryptography, it produced a hybrid cryptosystem that we called a Pretty Good Privacy (PGP).In this dissertation, we will only provide basic knowledge of PGP with simple explanation based on research done by security experts around the world. Through out this thesis, we will look into the history of cryptography and the basic concept of how PGP works and its key components. We also will look into the possible attack available for key components used in PGP. At the end of this paper, we will discuss on possible attack of PGP in general without specifying on any key component used in PGP.